2009
DOI: 10.1289/ehp.0900613
|View full text |Cite
|
Sign up to set email alerts
|

Diarylheptanoid Phytoestrogens Isolated from the Medicinal Plant Curcuma comosa : Biologic Actions in Vitro and in Vivo Indicate Estrogen Receptor–Dependent Mechanisms

Abstract: BackgroundDiarylheptanoids isolated from Curcuma comosa Roxb. have been recently identified as phyto estrogens. However, the mechanism underlying their actions has not yet been identified.ObjectivesWe characterized the estrogenic activity of three active naturally occurring diarylheptanoids both in vitro and in vivo.MethodsWe characterized mechanisms of estrogenic action of the diarylheptanoids (3S)-1,7-diphenyl-(6E)-6-hepten-3-ol (D1), 1,7-diphenyl-(6E)-6-hepten-3-one (D2), and (3R)-1,7-diphenyl-(4E,6E)-4,6-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
77
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 56 publications
3
77
0
Order By: Relevance
“…High-dose alcohol alters normal embryogenesis and is a known risk factor for oral clefts and one explanation for this association (Munger et al, 1996;DeRoo et al, 2008). Chinese herbs (e.g., curcuma comosa, angelica sinensis) in some supplements may have estrogenic effects, which could alter oral cleft risk (Winuthayanon et al, 2009;Natural Standard, 2013). Some herbs (angelica sinesis) may be prepared in or combined with alcohol (Natural Standard, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-dose alcohol alters normal embryogenesis and is a known risk factor for oral clefts and one explanation for this association (Munger et al, 1996;DeRoo et al, 2008). Chinese herbs (e.g., curcuma comosa, angelica sinensis) in some supplements may have estrogenic effects, which could alter oral cleft risk (Winuthayanon et al, 2009;Natural Standard, 2013). Some herbs (angelica sinesis) may be prepared in or combined with alcohol (Natural Standard, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we hypothesized that liver intake, a micronutrient-dense food, decreases the risk of having an affected child. Menstrual regulation supplements may contain alcohol or herbs with estrogenic effects that could increase oral cleft risk (Winuthayanon et al, 2009;Natural Standard, 2013). We examined other environmental risk factors, including maternal diabetes and cold, in relation to CL ± P risk.…”
mentioning
confidence: 99%
“…5) Our unpublished in silico-study also found that all compounds exhibited affinity to estrogen receptors and that supported the findings of previous studies in estrogen-like activity of 2 and 3. [18][19][20] Meanwhile, other diarylheptanoids isolated previously by Suksamrarn et al 5) are minor components, indicating a lower degree of potential markers. A very small amount in the plant rhizomes was also found for (6E)-1,7-diphenylhept-6-en-3-one.…”
mentioning
confidence: 91%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Pure compounds and plant extracts of C. comosa exhibited several pharmacological activities including anti-allergic, 9) anti-inflammatory, 13) anti-melanogenesis, 8) hepatoprotective, 16) bonesparing 17) and estrogenic effects. 20) Among these pharmacological activities, the estrogen-like property of the C. comosa has evoked public interest and led to research studies for its application as a hormone replacement therapy instead of estrogen treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation